Physical and Psychological Health of Nursing Staff During the Pandemic: Effect of Stress - Rohini Panchbhai; Rucha Lohi; Shaini Suraj; Vijay Babar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Stress is part of life and it affects the people in different ways. If stress is not managed properly it can lead toanger, frustration or depression. High stress levels can cause physical or psychological issues. It might causeheadache, weight loss or weight gain, dizziness, teeth grinding, lack of sleep, laziness, body pain, anger,irritation, anxiety or depression. The nursing staff being part of a sector which falls under essential serviceswas at work in hospitals during the pandemic COVID 19. They had to report to services in spite of the factthat they were equally exposed to the risk of getting the infection. In such situation the nursing staff wasworking under stress. This study aims to investigate the relationship between the stress and health of nursingstaff employed in the COVID 19 ward.